2-Mercaptomethyl-thiazolidines use conserved aromatic–S interactions to achieve broad-range inhibition of metallo-β-lactamases. Issue 8 (13th January 2021) - Rossi, Maria-Agustina; Martinez, Veronica; Hinchliffe, Philip; Mojica, Maria F.; Castillo, Valerie; Moreno, Diego M.; Smith, Ryan; Spellberg, Brad; Drusano, George L.; Banchio, Claudia; Bonomo, Robert A.; Spencer, James; et al.
Abstract : Metallo-β-lactamases (MBLs) are major culprits of resistance to carbapenems in bacteria. A series of thiazolidines are potent MBL inhibitors, restoring the activity of carbapenems. Metal binding and sulphur–π interactions are key to inhibition. Abstract : Infections caused by multidrug resistant (MDR) bacteria are a major public health threat. Carbapenems are among the most potent antimicrobial agents that are commercially available to treat MDR bacteria. Bacterial production of carbapenem-hydrolysing metallo-β-lactamases (MBLs) challenges their safety and efficacy, with subclass B1 MBLs hydrolysing almost all β-lactam antibiotics. MBL inhibitors would fulfil an urgent clinical need by prolonging the lifetime of these life-saving drugs. Here we report the synthesis and activity of a series of 2-mercaptomethyl-thiazolidines (MMTZs), designed to replicate MBL interactions with reaction intermediates or hydrolysis products. MMTZs are potent competitive inhibitors of B1 MBLs in vitro ( e.g., K i = 0.44 μM vs. NDM-1). Crystal structures of MMTZ complexes reveal similar binding patterns to the most clinically important B1 MBLs (NDM-1, VIM-2 and IMP-1), contrasting with previously studied thiol-based MBL inhibitors, such as bisthiazolidines (BTZs) or captopril stereoisomers, which exhibit lower, more variable potencies and multiple binding modes. MMTZ binding involves thiol coordination to the Zn(ii ) site and extensive hydrophobic interactions, burying the inhibitor more deeply within the active site than d /l -captopril. Unexpectedly, MMTZ binding features a thioether–π interaction with a conserved active-site aromatic residue, consistent with their equipotent inhibition and similar binding to multiple MBLs. MMTZs penetrate multiple Enterobacterales, inhibit NDM-1 in situ, and restore carbapenem potency against clinical isolates expressing B1 MBLs. Based on their inhibitory profile and lack of eukaryotic cell toxicity, MMTZs represent a promising scaffold for MBL inhibitor development. These results also suggest sulphur–π interactions can be exploited for general ligand design in medicinal chemistry.